A complex network framework for the efficiency and resilience trade-off in global food trade. (23rd September 2021) - Karakoc, Deniz Berfin; Konar, Megan
Abstract: Global food trade is crucial for food security and availability. Trade is typically optimized to promote efficiency, whereas resilience is increasingly being recognized as another important objective. However, it is not clear if prioritizing resilience comes at the expense of efficiency or if the two objectives can be promoted simultaneously. We develop a complex network framework to assess the relationship between efficiency and resilience of food trade for the last half century. There is a competitive relationship between efficiency and resilience when only network topology is considered. However, a cooperative relationship between efficiency and resilience exists when the intensity of trade connections is accounted for. Policy makers can use this framework to evaluate the relationship between efficiency and resilience in critical supply chains.